Locke - Rickless, Samuel Charles, 1964- (Hoboken, NJ : Wiley-Blackwell, 2014)
"Maps the full range of John Locke's highly influential ideas, which even today remain at the heart of debates about the nature of reality and our knowledge of it, as well as our moral and political rights and duties."--Provided by publisher.
11.3 Punishment and Slavery11.4 Property; 11.5 Family; chapter 12: political philosophy; 12.1 Political Society; 12.2 Legitimate Rule; 12.3 Varieties of Illegitimate Rule; 12.4 Toleration; index
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Locke, John, -- 1632-1704.; Locke, John, -- 1632-1704.; Locke, John, -- 1632-1704.; Locke, John, -- 1632-1704.; Locke, John, -- 1632-1704; Essay concerning human understanding (Locke, John); Two treatises of government (Locke, John); PHILOSOPHY -- History & Surveys -- Modern; Electronic books; Electronic books